The Effect of Cooperative Learning Model on Elementary School Students’ Affective Learning Outcomes: A Meta-Analysis - Ma'as Shobirin; Fitria Martanti; Ummu Jauharin Farda; Ersila Devy Rinjany (UIN Siber Syekh Nurjati Cirebon, 2025)
AbstractThis meta-analysis aims to examine the effect of cooperative learning on elementary school students’ affective learning outcomes after the implementation of the cooperative learning model. 40 relevant studies, through online databases, including Google Scholar, DOAJ, ERIC, Springer, Elsevier, and ResearchGate, were identified. Of these, 12 studies met the inclusion criteria and provided usable data, yielding 16 artifacts. Data from 16 artifacts, including sample sizes, means, and standard deviations, were collected using descriptive analysis. The data analysis utilized meta-analysis techniques, including effect size calculation, heterogeneity testing, summary effect estimation using a random-effects model, and the assessment of potential publication bias through forest plots. Those analyses utilized JASP software. The results showed that: (1) The effect size (ES) for affective learning outcomes of elementary school students was 77.06, with a 95% confidence interval (CI) ranging from 73.34 to 81.77. The hypothesis test produced a z value of 0.4035, which is smaller than the critical value (z = 1.96), leading to the acceptance of the null hypothesis (H₀) and the rejection of the alternative hypothesis (Hₐ); (2) Although there is a slight asymmetry in the funnel diagram indicating potential publication bias, the statistically insignificant Egger regression test (z = -0.1078, p = 0.914) supports the robustness of the meta-analysis, which confirms that the cooperative learning model produces moderate to high affective learning outcomes in elementary school students. This finding indicates that although cooperative learning can positively influence students' affective learning outcomes, the observed effect size is not statistically significant at α = 0.05. Thus, it is recommended that future studies refine the design and implementation of cooperative learning strategies to increase their effectiveness and achieve statistically significant improvements in elementary school students' affective learning outcomes.Keywords: affective learning outcomes, cooperative learning, meta-analysis.AbstrakMeta-analisis ini bertujuan untuk menguji pengaruh pembelajaran kooperatif terhadap hasil belajar afektif siswa sekolah dasar setelah penerapan model pembelajaran kooperatif. Sebanyak 40 studi relevan, melalui basis data daring, termasuk Google Scholar, DOAJ, ERIC, Springer, Elsevier, dan ResearchGate, diidentifikasi. Dari jumlah tersebut, 12 studi memenuhi kriteria inklusi dan menyediakan data yang dapat digunakan, menghasilkan 16 artefak. Data dari 16 artefak, termasuk ukuran sampel, rata-rata, dan deviasi standar, dikumpulkan menggunakan analisis deskriptif. Analisis data menggunakan teknik meta-analisis, termasuk perhitungan ukuran efek, pengujian heterogenitas, estimasi efek ringkasan menggunakan model efek acak, dan penilaian potensi bias publikasi melalui plot hutan. Analisis tersebut menggunakan perangkat lunak JASP. Hasil penelitian menunjukkan bahwa: (1) Besarnya efek (ES) terhadap hasil belajar afektif siswa sekolah dasar adalah 77,06, dengan interval kepercayaan (CI) 95% berkisar antara 73,34 hingga 81,77. Uji hipotesis menghasilkan nilai z sebesar 0,4035, yang lebih kecil daripada nilai kritis (z = 1,96), sehingga menyebabkan diterimanya hipotesis nol (H₀) dan ditolaknya hipotesis alternatif (Hₐ); (2) Meskipun terdapat sedikit asimetri pada diagram corong yang mengindikasikan potensi bias publikasi, uji regresi Egger yang secara statistik tidak signifikan (z = -0,1078, p = 0,914) mendukung kekokohan meta-analisis, yang menegaskan bahwa model pembelajaran kooperatif menghasilkan hasil belajar afektif sedang hingga tinggi pada siswa sekolah dasar. Temuan ini menunjukkan bahwa meskipun pembelajaran kooperatif dapat memengaruhi hasil belajar afektif siswa secara positif, besarnya efek yang teramati tidak signifikan secara statistik pada α = 0,05. Oleh karena itu, disarankan agar penelitian masa depan menyempurnakan desain dan implementasi strategi pembelajaran kooperatif untuk meningkatkan efektivitasnya dan mencapai peningkatan yang signifikan secara statistik pada hasil belajar afektif siswa sekolah dasar.Kata kunci: hasil pembelajaran afektif, pembelajaran kooperatif, meta-analisis.